Magnitude of and Prognostic Factors Associated With 1‐Year Mortality After Hospital Discharge for Acute Decompensated Heart Failure Based on Ejection Fraction Findings. Issue 12 (December 2015) - Coles, Andrew H.; Tisminetzky, Mayra; Yarzebski, Jorge; Lessard, Darleen; Gore, Joel M.; Darling, Chad E.; Goldberg, Robert J.
Abstract : Background: Limited data exist about the magnitude of and the factors associated with prognosis within 1 year for patients discharged from the hospital after acute decompensated heart failure. Data are particularly limited from the more generalizable perspective of a population‐based investigation and should be further stratified according to currently recommended ejection fraction (EF) findings. Methods and Results: The hospital medical records of residents of the Worcester, Massachusetts, metropolitan area who were discharged after acute decompensated heart failure from all 11 medical centers in central Massachusetts during 1995, 2000, 2002, 2004, and 2006 were reviewed. The average age of the 4025 study patients was 75 years, 93% were white, and 44% were men. Of these, 35% (n=1414) had reduced EF (≤40%), 13% (n=521) had borderline preserved EF (41–49%), and 52% (n=2090) had preserved EF (≥50%); at 1 year after discharge, death rates were 34%, 30%, and 29%, respectively ( P =0.03). Older age, a history of chronic obstructive pulmonary disease, systolic blood pressure findings <150 mm Hg on admission, and hyponatremia were important predictors of 1‐year mortality for all study patients, whereas several comorbidities and physiological factors were differentially associated with 1‐year death rates in patients with reduced, borderline preserved, and preserved EF. Conclusions: This population‐based study highlights the need for further contemporary research into the characteristics, treatment practices, natural history, and long‐term outcomes of patients with acute decompensated heart failure and varying EF findings and reinforces ongoing discussions about whether different treatment guidelines may be needed for these patients to design more personalized treatment plans.